ISOLATION, PURIFICATION, AND CHARACTERIZATION OF PORCINE SKIN COLLAGEN: ANALYSIS OF THE GLYCINE, PROLINE, AND HYDROXYPROLINE COMPONENTS USING HIGH-PERFORMANCE LIQUID CHROMATOGRAPHY - Andayani, Ayu Aditya; Harmita, Harmita; Maggadani, Baitha Palanggatan (International Journal of Applied Pharmaceutics, 2018)
Objective: The aim of this study is to produce collagen through the extraction and isolation of porcine skin. Methods: Collagen from porcine skin (Sus scrofa domesticus) was isolated, purified, and characterized. Major amino acid content of collagen (glycine, proline, and hydroxyproline) was determined. Samples were extracted with 0.5 N acetic acid and precipitated with 0.9 M NaCl. Characterization tests included those to determine the organoleptic content, pH, Fourier-transform infrared analysis, moisture content, ash content, viscosity, and Masson's trichrome staining on collagen tissue. The collagen was further analyzed using high-performance liquid chromatography using C-18® column and a fluorescence detector at 265 nm and 320 nm, acetic buffer (pH 4.2)–acetonitrile (55:45) as mobile phase, and optimum flow rate of 0.8 mL/min. Results: Our findings indicated that the best method for isolating collagen was with 0.1 M NaOH expressed by average contents of glycine, proline, and hydroxyproline in collagen which were 33.663±0.215%, 12.333±0.128%, and 11.303±0.354%, respectively. Conclusion: Porcine collagen has been successfully obtained with this method.